miR-541-3p Promoted Porcine Reproductive and Respiratory Syndrome Virus 2 (PRRSV-2) Replication by Targeting Interferon Regulatory Factor 7 - Xibao Shi; Yuanhao Yang; Xiaozhuan Zhang; Xiaobo Chang; Jing Chen; Chao Wang; Aiping Wang; Jianhua Wang; Jianru Qin; Xianlong Ye; Wei Jin; Gaiping Zhang (Viruses, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is a disease caused by PRRS virus (PRRSV), which seriously harms the pig industry. Revealing the mechanism by which PRRSV inhibits immune response will help prevent and control PRRS. Here, we found that PRRSV-2 may hijack host miR-541-3p to inhibit host innate immune response. Firstly, this work showed that miR-541-3p mimics could facilitate the replication of PRRSV-2 and the results of the quantitative real time polymerase chain reaction (qRT-PCR) showed that PRRSV-2 could up-regulate the expression of miR-541-3p in MARC-145 cells. Since previous studies have shown that type I interferon could effectively inhibit the replication of PRRSV-2, the present work explored whether miR-541-3p regulated the expression of type I interferon and found that miR-541-3p could negatively regulate the transcription of type I interferon by targeting interferon regulatory factor 7 (IRF7). More importantly, PRRSV-2 infection could down-regulate the expression of IRF7 and over-expression of IRF7 could down-regulate the replication of PRRSV-2 in MARC-145 cells. In conclusion, PRRSV-2 infection up-regulated the expression of miR-541-3p to promote its replication in MARC-145 cells, since miR-541-3p can negatively regulate the transcription of type I interferon by targeting IRF7.